Fast-tracking development and regulatory approval of COVID-19 vaccines in the EU: A review of ethical implications - Beretta, Giorgia (Bioethics, 2023)
The rapid spread of SARS-CoV-2 worldwide has triggered intense activity in the field of biotechnology, leading to the development and regulatory approval of multiple COVID-19 vaccines in less than 1 year while raising sustained scrutiny as to the ethical issues associated with this process. This article pursues a twofold objective. First, it reconstructs and provides a thorough overview of the different steps, from clinical trial design to regulatory procedures, underpinning the “fast-tracking” of COVID-19 vaccine R&D and approval. Second, drawing on a review of published literature, the article identifies, outlines, and analyzes the most ethically challenging aspects related to such process, including concerns around vaccine safety, issues in study design, the enrollment of study participants, and the challenges in obtaining valid informed consent. By scrutinizing relevant aspects of COVID-19 vaccine development and regulatory processes leading to market authorization, this article ultimately aims to provide a comprehensive overview of the regulatory and ethical issues underpinning the roll-out of this key pandemic-containment technology worldwide.